ANALISIS KURIKULUM DIKLAT PREPARASI DAN PENCUCIAN BATUBARA DALAM MENINGKATKAN PENYELENGGARAAN DIKLAT TEKNIS BATUBARA KUALITAS RENDAH DI PPSDM GEOMINERBA - Wanda Adinugraha (PPSDM Geominerba, 2020)
The implementation of the duties and functions of the organization, over the past few years, the Center for the Development of Mineral and Coal Geological Human Resources held Technical Training in the field of coal which includes Coal Handling Training, Coal Stockpile Management Training, and Blasting Implementation Training at Mineral Open Mine and coal. The Education and Training Program has not yet fully supported the use of low grade coal, due to the unavailability of a curriculum in this regard. Through the Causal Map analysis and mapping, it is known that the causes of the problems mentioned above are: the curriculum for the training of low-grade coal processing has not yet been prepared, which is caused by a specific problem: the unavailability of curriculum standards for technical training in the field of coal which includes the use and increase of the added value of low-grade coal. Furthermore, by conducting a USGR analysis, an alternative problem solving is obtained, namely by completing the existing coal training technical program through the preparation of a curriculum for coal preparation and washing training. The organization had the potential to overcome the main problems faced, a coordinated work plan was developed which included setting targets, indicators, programs and activities for the preparation of the Coal Training for Preparation and Coal Washing.